Since it has the same base,you keep the base out and add on the exponent on the top x^5x^7=x^7+5 which =12 then you just multiply the exponent which will be (x^3)^2which =x^3*2that is equal to x^6>and last you subtract the exponent from the top and bottom=x^12-6=x^6

Exercise 12.

You multiply all the exponents in the problem 5,3,4,2 you add the exponents on the top than you divide the bottom exponents y^17/8

## Exercise 11.

Since it hasthe same base,you keep the base out and add on the exponent on the top x^5x^7=x^7+5 which =12 then you just multiply the exponent which will be (x^3)^2which =x^3*2that is equal to x^6>and last you subtract the exponent from the top and bottom=x^12-6=x^6## Exercise 12.

You multiply all the exponents in the problem 5,3,4,2 you add the exponents on the top than you divide the bottom exponents y^17/8

## Exercise 13.